THE USE OF TIO2-ZEOLIT AS A CATALYST ON THE DEGRADATION PROCESS OF ERIONIL RED DYE - Agustin Sumartono; Winarti Andayani (Universitas Gadjah Mada, 2007)
Degradation of erionil red dye using photo catalytic processes with TiO2-zeolit as a catalyst was carried out. Degradation of the dye was observed in 10 L volume, and erionil red dye was used as a model of organic pollutant. The parameters examinated were intensity of the spectrum, the decrease of pH, percentage of degradation, and the efectifity TiO2-zeolit as a catalyst. The use of UV lamp and TiO2-zeolit as a catalyst showed a good results because the dye could be degraded. This could be seen from the decreasing of the intensity of the spectrum 24 h after illumination. The pH of erionil red increased from around 4 into 5.5 which is still acidic. Effectivity of TiO2 composit as a catalyst could be used only two times. The compound resulted from degradation that could be detected using HPLC was oxalic acid.